2010
DOI: 10.1038/ismej.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Ca-phosphate precursors for Ca-carbonate biominerals mediated by Chromohalobacter marismortui

Abstract: Although diverse microbial metabolisms are known to induce the precipitation of carbonate minerals, the mechanisms involved in the bacterial mediation, in particular nucleation, are still debated. The study of aragonite precipitation by Chromohalobacter marismortui during the early stages (3-7 days) of culture experiments, and its relation to bacterial metabolic pathways, shows that: (1) carbonate nucleation occurs after precipitation of an amorphous Ca phosphate precursor phase on bacterial cell surfaces and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 51 publications
(56 reference statements)
6
55
0
Order By: Relevance
“…The concentration of NaCl was set as 3,5,8,10,12,15,18, and 20 % (w/v). The above liquid seed was inoculated into the liquid culture medium with different concentration of NaCl by 1 % of inoculation volume and incubated at 130 rpm and 30 °C.…”
Section: Growth Of C Israelensis Ld532 Bacteria At Different Nacl Comentioning
confidence: 99%
See 2 more Smart Citations
“…The concentration of NaCl was set as 3,5,8,10,12,15,18, and 20 % (w/v). The above liquid seed was inoculated into the liquid culture medium with different concentration of NaCl by 1 % of inoculation volume and incubated at 130 rpm and 30 °C.…”
Section: Growth Of C Israelensis Ld532 Bacteria At Different Nacl Comentioning
confidence: 99%
“…In recent decades, many microbial fossils have been discovered in biolith, such as cyanobacteria, which confirmed that microbes were closely associated with the diagenesis of minerals. A large number of researchers have studied the ability of bacteria to precipitate minerals in the natural environment and laboratory based on previous research findings of the biolith such as stromatolite, oncolite, dendrite, and thrombolite [2][3][4][5][6][7][8][9][10]. Therefore, the role of microorganisms in the precipitation of a wide variety of carbonates has been generally acknowledged in recent years [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, many microbial fossils, such as those of cyanobacteria, have been discovered in bioliths, which confirms that microbes are closely associated with the diagenesis of minerals. Many researchers have investigated the ability of bacteria to precipitate minerals in natural environments and the laboratory, based on previous research findings on bioliths, such as stromatolites, oncolites, dendrites, and thrombolites [2][3][4][5][6][7][8][9][10]. Therefore, the role of microorganisms in the precipitation of a wide variety of carbonates has been generally acknowledged in recent years [11].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of mineralization induced by halophilic bacteria has also been studied by a number of researchers. The cellular envelopes of bacteria provided nucleation sites in the process of carbonate precipitation [5-3 of 23 8,10,28]. The EPS and the cell walls were identified as the nucleation sites [32].…”
Section: Introductionmentioning
confidence: 99%